2015
DOI: 10.1055/s-0035-1546468
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of World Health Organization Grades II and III Intracranial Meningiomas in the United States

Abstract: Background. Because World Health Organization (WHO) grades II and III meningiomas are relatively uncommon, there is limited literature on the descriptive epidemiology of these tumors, and the existing literature predates the 2000 WHO classification revisions. Our purpose was to provide a modern, population-based study of the descriptive epidemiology of WHO II and III meningiomas in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 19 publications
2
31
0
1
Order By: Relevance
“…As in our previous work, we found that while pediatric meningiomas may include relatively more aggressive subtypes, young age is overall associated with reduced all-cause mortality. 4 In regard to sex, across all ages overall, meningiomas were more frequent in females than in males, but malignancy 19 and mortality 3,20,21 were greater in males than females. Also concordant with previous reports, black race and larger tumor size were found to be adverse prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in our previous work, we found that while pediatric meningiomas may include relatively more aggressive subtypes, young age is overall associated with reduced all-cause mortality. 4 In regard to sex, across all ages overall, meningiomas were more frequent in females than in males, but malignancy 19 and mortality 3,20,21 were greater in males than females. Also concordant with previous reports, black race and larger tumor size were found to be adverse prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…We report on the meningioma data up to the November 2017 SEER release, but our observational results are broadly consistent with what has been reported in previous epidemiological literature on meningiomas. From 2004 to 2010, Kshettry et al 19 reported that WHO grade II and III meningiomas accounted for 4.2% and 1.2% of newly diagnosed meningiomas, respectively. Likewise, after exclusions, we identified a total of 62,844 meningiomas for the period between 2004 and 2015, of which 4.0% were coded as borderline malignant and 0.9% as malignant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, meningiomas are twice as common in females as in males . Histologically, most of the adult meningiomas are WHO grade I (approximately 95%), with grade II and III tumors occurring less frequently (4.2% and 1.2%) …”
Section: Introductionmentioning
confidence: 99%
“…Brain invasion in the context of otherwise benign histological appearance itself defines the tumour as grade II, thus broadening the inclusion criteria for grade II. Indeed, this has been reflected in the increase in the incidence of grade II and decrease of grade III meningiomas [9]. Backer-Grøndahl et al [1] Despite progressive improvements in the classification of meningiomas, we know from our clinical observations that atypical meningiomas are far from being homogeneous in their natural history and response to treatment.…”
mentioning
confidence: 99%